Impacts of Cognitive Behavioral Therapy for Insomnia and Pain on Sleep in Women with Gynecologic Malignancies: A Randomized Controlled Trial. Issue 4 (4th July 2022) - Padron, Adaixa; McCrae, Christina S.; Robinson, Michael E.; Waxenberg, Lori B.; Antoni, Michael H.; Berry, Richard B.; Castagno, Jacqueline; Schultz, Gregory; Kacel, Elizabeth L.; Ulfig, Chantel; Garey, Stephanie; Patidar, Seema; et al.
ABSTRACT: Insomnia is an adverse cancer outcome impacting mood, pain, quality of life, and mortality in cancer patients. Cognitive Behavioral Therapy (CBT) is an evidence-based treatment for diverse psychophysiological disorders, including pain and insomnia. Primarily studied in breast cancer, there is limited research on CBT within gynecology oncology. This study examined CBT effects on subjective and behavioral sleep outcomes: Sleep Efficiency (SE), Sleep Quality (SQ), Total Wake Time (TWT), Sleep Onset Latency (SOL), and Wake After Sleep Onset (WASO). Thirty-five women with insomnia status/post-surgery for gynecologic cancer were randomized to CBT for insomnia and pain (CBTi.p., N = 18) or Psychoeducation ( N = 17). Sleep was assessed via sleep diaries and wrist-worn actigraphy at baseline (T1), post-intervention (T2), and two-month follow-up (T3). Intent-to-treat analyses utilizing mixed linear modeling examined longitudinal group differences on sleep controlling for age and advanced cancer. All participants demonstrated improved (1) subjective SE (0.5, p < .01), SOL (−1.2, p < .01), TWT (−1.2, p < .01), and (2) behavioral SE (0.1, p = .02), TWT (−1.2, p = .03), WASO (−0.8, p < .01) across time. Group-level time trends were indicative of higher subjective SE (6.8, p = .02), lower TWT (−40.3, p = .01), and lower SOL (−13.0, p = .05) in CBTi.p. compared to Psychoeducation. Supplemental analyses examining clinical significance and acute treatment effects demonstrated clinical improvements in SE (T1), TWT (T2, T3), and SOL (T3). Remaining effects were not significant. Despite lacking power to detect interaction effects, CBTi.p. clinically improved sleep in women with gynecologic cancers and insomnia during the active treatment phase. Future research will focus on developing larger trials within underserved populations.